Case report of acute hepatorenal failure induced by third-line treatment with tislelizumab in a patient with cholangiocarcinoma: was influenza virus the culprit? - Zhang, Xuebing; Zhang, Xia; Yin, Hang; Zhang, Weiguo; Zhang, Bin (Frontiers in Immunology, 2025)
A 72-year-old male diagnosed with cholangiocarcinoma was initiated on third-line therapy comprising Tislelizumab and Anlotinib. Within four days of treatment, he developed fulminant hepatic injury concurrent with acute kidney injury. Despite aggressive management with high-dose glucocorticoids, hepatoprotective agents, comprehensive supportive care, and subsequent anti-infective therapy, his clinical status declined rapidly. In view of the grave prognosis and the family’s decision to decline intensive interventions such as plasma exchange, the patient ultimately succumbed to multiorgan failure. This case highlights a potential synergistic interaction between concomitant infection (e.g.,influenza virus) and immune checkpoint inhibitor(ICI) therapy, possibly mediated through enhanced antigenic stimulation and loss of immunoregulatory control, culminating in exaggerated immune activation. This mechanism may have profoundly amplified ICI-related toxicity, leading to fatal multiorgan irAEs. Regarding the issue of immune storms, it is challenging for clinical practice to provide favorable outcomes for patients, and we need to remain highly vigilant.